ANALISIS DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI KARET DI DESA KUAPAN KECAMATAN TAMBANG KABUPATEN KAMPAR - Sakina Suzianti; Shorea Khaswarina; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2021)
Income distribution is an analysis used to see the level of income distribution in a certain class. Income distribution is obtained by identifying various sources of income of sample farmers, namely income from rubber farming, non-rubber farming income and non-agricultural income. In the study entitled Distribution Analysis of Household Income of Rubber Farmers in Kuapan Village, Tambang District, Kampar Regency, the number of rubber farmers sampled was 50 farmers which were divided into 2 groups, namely non-owner tapping farmers (15 sample farmers) and tapping farmers as well as owners (35 farmers). sample farmers) with proportionate stratified random sampling and snowball sampling. Based on the results of the study, there was no income inequality either in the group of non-owner tapping farmers and the group of tapping farmers as well as owners. Where the combined Gini ratio index is 0.19. Based on the research, equity in both groups of farmers can occur because (1) tapping farmers have other income besides rubber farming (2) non-owner tapping farmers benefit from a profit-sharing system with a ratio of 1: 2 (3) tapping farmers as well as owners have to pay maintenance costs. and land clearing (4) non-owner tapping farmers only incur costs for tools and operational materials.